Study on the influence of electron beam irradiation on the thermal, mechanical, and rheological properties of ethylene‐octene copolymer with high comonomer content. Issue 5 (14th September 2012) - Poongavalappil, Sameepa; Svoboda, Petr; Theravalappil, Rajesh; Svobodova, Dagmar; Danek, Michal; Zatloukal, Martin
Abstract Ethylene‐octene copolymer (EOC) was irradiated using electron beam irradiation at different dosages (30, 60, 90, and 120 kGy). Effect of irradiation dosage on thermal and mechanical properties was studied. When compared to low density polyethylene, EOC exhibited higher degree of crosslinking reflected in increased gel content, higher elastic modulus (G′), and lower tan δ obtained by rheology measurement at 150°C. Crosslinking caused improvement in high‐temperature creep and room temperature and also elevated temperature elastic properties. Differential scanning calorimetry revealed that e‐beam irradiation has caused a gradual reduction in crystallinity and a presence of a fraction with higher melting temperature. In the case of EOC, as the extent of crosslinking increased, stress at break showed an increasing trend whereas irradiation dosage had an inverse effect on elongation at break. Radiation dosage has positive effect on thermal stability estimated by thermogravimetric analysis. After 30 min of thermal degradation at 220°C, slightly higher CO peak for crosslinked sample was found by Fourier transform infrared spectroscopy while for room temperature samples no CO peak was detected. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013